2018
DOI: 10.3389/fimmu.2018.02750
|View full text |Cite
|
Sign up to set email alerts
|

CXCL16/CXCR6 Axis Drives Microglia/Macrophages Phenotype in Physiological Conditions and Plays a Crucial Role in Glioma

Abstract: Microglia are patrolling cells that sense changes in the brain microenvironment and respond acquiring distinct phenotypes that can be either beneficial or detrimental for brain homeostasis. Anti-inflammatory microglia release soluble factors that might promote brain repair; however, in glioma, anti-inflammatory microglia dampen immune response and promote a brain microenvironment that foster tumor growth and invasion. The chemokine CXCL16 is expressed in the brain, where it is neuroprotective against brain isc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
83
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 82 publications
(90 citation statements)
references
References 49 publications
2
83
1
Order By: Relevance
“…The inflammatory response that follows the initial ischemic insult is a key mechanism of secondary degeneration (Jin et al, 2010;Hamzei Taj et al, 2016). The critical roles of the NLRP3 inflammasome during stroke have been documented in many studies (Lepore et al, 2018; FIGURE 9 | Meisoindigo treatment suppresses the activation of the TLR-4/NF-κB/NLRP3 signaling pathway after stroke. (A) Representative western blot showing that Mei treatment reduces the expression and phosphorylation of TLR-4/NF-κB/NLRP3 signaling pathway-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…The inflammatory response that follows the initial ischemic insult is a key mechanism of secondary degeneration (Jin et al, 2010;Hamzei Taj et al, 2016). The critical roles of the NLRP3 inflammasome during stroke have been documented in many studies (Lepore et al, 2018; FIGURE 9 | Meisoindigo treatment suppresses the activation of the TLR-4/NF-κB/NLRP3 signaling pathway after stroke. (A) Representative western blot showing that Mei treatment reduces the expression and phosphorylation of TLR-4/NF-κB/NLRP3 signaling pathway-related proteins.…”
Section: Discussionmentioning
confidence: 99%
“…Primary microglia were isolated from the cortex of newborn (postnatal day 0-2) C57BL/6 J mice by mild trypsinization as previously described [44]. Briefly, the cortex was chopped and digested into a single cell suspension which was incubated in DMEM/F-12 containing 10% FBS and 100 U/ml 1% penicillin/streptomycin.…”
Section: Cell Culturementioning
confidence: 99%
“…The detection of increased levels of mRNA for the ligands for each of CXCR3 and CXCR6 suggests that both of these two chemokine receptors can function in the brains of the recipients of the immune T cells. Both CXCR3 and CXCR6 can be expressed on microglia and macrophages (16)(17)(18)(19). Since our recent studies demonstrated that both Iba1 ϩ microglia and Ly6C ϩ inflammatory macrophages accumulate to T. gondii cysts during CD8 ϩ cytotoxic T cell-mediated elimination of the cysts (13), it is possible that CXCR3 and CXCR6 mediate the accumulation of these phagocytes to the sites of anticyst immune responses once CD8 ϩ T cells initiate this process through their perforin-mediated activities.…”
Section: Resultsmentioning
confidence: 99%
“…ICOS is one of T cell costimulation molecules (14,15). CXCR3, CXCR6 (16)(17)(18)(19), and IL-18R1 are the molecules involved in recruitment and/or activation of microglia and macrophages (20,21). Therefore, the results of the present study suggest that ICOS plays an important role in activating CD8 ϩ cytotoxic T cells to initiate attacking T. gondii cyst-holding cells and that CXCR3, CXCR6, and IL-18R1 are involved in recruiting and activating the phagocytes corresponding to the T cellattacked cysts for eradicating bradyzoites located within the cysts for their elimination.…”
mentioning
confidence: 99%